2017
DOI: 10.1590/1980-5918.030.004.ao13
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and duration of hemodialysis in patients with chronic kidney disease (CKD): a cross-sectional study

Abstract: Introduction: Quality of life (QoL) of hemodialysis patients is a major evaluative marker currently measured, while treatment time is a clinical determinant associated with impaired QOL. Objective: To evaluate QOL in individuals undergoing hemodialysis (HD) considering treatment time and the presence of comorbidities. Methods: A cross-sectional study conducted in the hemodialysis unit of the Hospital das Clínicas da Universidade Federal de Pernambuco (HC-UFPE). We studied patients with Chronic Kidney Disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
8
1
5
Order By: Relevance
“…About HD duration, and PTH and S. creatinine, Study was done by Barbosa et al which does not coincide with the results. There were no differences observed between those who were below or above 36 months of treatment and PTH, S. creatinine [20]. Some other studies also found no changes of laboratorial factors (urea, creatinine, PTH (ParaThyroid Hormone) over the duration of disease which makes us think of the possibility of other factors occurring besides those investigated [21,22].…”
Section: Discussionmentioning
confidence: 71%
“…About HD duration, and PTH and S. creatinine, Study was done by Barbosa et al which does not coincide with the results. There were no differences observed between those who were below or above 36 months of treatment and PTH, S. creatinine [20]. Some other studies also found no changes of laboratorial factors (urea, creatinine, PTH (ParaThyroid Hormone) over the duration of disease which makes us think of the possibility of other factors occurring besides those investigated [21,22].…”
Section: Discussionmentioning
confidence: 71%
“…It should be noted that the dialysis treatment routine is continuous and prolonged leading the individual to depend on a machine for survival and bringing about psychological and physical wear and tear, and it is generally observed that fatigue and / or lack of after the hemodialysis sessions. 14 It is inferred that fatigue can be one of the determining factors for problems related to sexuality. It is evident, in the speech of I 19, that reports the income.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing has changed. (Interviewee,5,14,20,22,23,24,25,27,32,38) It has been noted in the reports that the issue of sexuality is intimately linked to healthy sexual intercourse, both biologically and emotionally, showing its importance to man. Wondering when they were happy with their sex life, most reported the following: Yes I am happy.…”
Section: In the Beginning I Had Depression So I Traveled A Lot And mentioning
confidence: 99%
See 2 more Smart Citations